2008
DOI: 10.1080/13854040701625846
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Brain Dysfunction of the Halstead-Reitan vs an Ability-Focused Neuropsychological Battery

Abstract: We compared the sensitivity to brain dysfunction of an ability focused neuropsychological battery (AFB), as a proxy for the core of a flexible battery, to the Halstead-Reitan Battery (HRB). The AFB was designed to represent constructs of language function, fine motor skill, working memory, processing speed, verbal and visual memory, and verbal and visual abstraction and problem solving. Receiver operating characteristic analysis (ROC) yielded an area under curve (AUC) of. 86 for the AFB, versus. 83 for the HRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 33 publications
1
17
1
1
Order By: Relevance
“…Our largest Cohen’s d effect size was −0.60 for the Grooved Pegboard test in the motor domain, which corresponds to a 61.8% overlap, meaning that approximately 20% of controls perform higher than any of the individuals with diabetes, and 20% of the individuals with diabetes perform worse than any of the controls (Zakzanis, 2001). These findings are similar to Larrabee and colleagues (Larrabee, Millis, & Meyers, 2008), who showed that the Grooved Pegboard test was more sensitive than any other test in the core Halstead-Reitan battery in a mixed neurologic sample; Trails B was the next most sensitive. Prior reviews have identified executive function, memory, and attention/ concentration as domains that appear particularly susceptible to cognitive dysfunction in persons with diabetes (Kawamura, Umemura, & Hotta, 2012; Kodl & Seaquist, 2008; Kumar, Looi, & Raphael, 2009; McCrimmon et al, 2012; Reijmer, van den Berg, Ruis, Kappelle, & Biessels, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Our largest Cohen’s d effect size was −0.60 for the Grooved Pegboard test in the motor domain, which corresponds to a 61.8% overlap, meaning that approximately 20% of controls perform higher than any of the individuals with diabetes, and 20% of the individuals with diabetes perform worse than any of the controls (Zakzanis, 2001). These findings are similar to Larrabee and colleagues (Larrabee, Millis, & Meyers, 2008), who showed that the Grooved Pegboard test was more sensitive than any other test in the core Halstead-Reitan battery in a mixed neurologic sample; Trails B was the next most sensitive. Prior reviews have identified executive function, memory, and attention/ concentration as domains that appear particularly susceptible to cognitive dysfunction in persons with diabetes (Kawamura, Umemura, & Hotta, 2012; Kodl & Seaquist, 2008; Kumar, Looi, & Raphael, 2009; McCrimmon et al, 2012; Reijmer, van den Berg, Ruis, Kappelle, & Biessels, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, statistical methods used to detect poor effort in neuropsychological practice and research included odds and likelihood ratios (Bieliauskas, Fastenau, Lacy, & Roper, 1997;Weinborn, Orr, Woods, Conover, & Feix, 2003), the aggregation across multiple indicators Larrabee, Millis, & Meyers, 2008), Bayesian average modeling Millis & Volinsky, 2001;Wolfe et al, 2010), and Bayesian latent class modeling (Mossman et al, 2012). In this context, we recently tested a Bayesian latent group analysis as a method that may help to improve classification accuracy of effort testing in various neuropsychological settings (Ortega, Wagenmakers, Lee, Markowitsch, & Piefke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For years, clinicians and researchers examined neuropsychological functioning using extensive batteries such as the Halstead-Reitan and Luria-Nebraska (Steinmeyer, 1984;Mittenberg, Kasprisin, & Farage, 1985;Kane, Parsons, Goldstein, & Moses, 1987;Katz & Goldstein, 1993;GrothMarnat, 2005;Sweeney, Slade, Ivins, Nemeth, Ranks, & Sica, 2007;Larrabee, Millis, & Meyers, 2008). One recent measure that may have some advantages due to its reduced time of administration is the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998;Randolph, Tierney, Mohr, & Chase, 1998).…”
mentioning
confidence: 98%